2021
DOI: 10.5194/hess-25-5065-2021
|View full text |Cite
|
Sign up to set email alerts
|

Spatially distributed impacts of climate change and groundwater demand on the water resources in a wadi system

Abstract: Abstract. Understanding current and possible future alterations of water resources under climate change and increased water demand allows for better water and environmental management decisions in arid regions. This study aims at analyzing the impact of groundwater demand and climate change on groundwater sustainability and hydrologic regime alterations in a wadi system in central Iran. A hydrologic model is used to assess streamflow and groundwater recharge of the Halilrood Basin on a daily time step under fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…It can simulate the quantity and quality of water resources from a hydrological response unit at the basin scale. SWAT is also suitable to assess the impact of climate change (Mahmoodi et al, 2021a), land cover change (Tigabu et al, 2019) and land use change (Wagner et al, 2023;McGinn et al, 2021), and watershed management practices on water resources (Mahmoodi et al, 2021b). Moreover, it has been proven to be capable of modeling in data-scarce regions (Wagner et al, 2012;Tigabu et al, 2023).…”
Section: Hydrologic Modelmentioning
confidence: 99%
“…It can simulate the quantity and quality of water resources from a hydrological response unit at the basin scale. SWAT is also suitable to assess the impact of climate change (Mahmoodi et al, 2021a), land cover change (Tigabu et al, 2019) and land use change (Wagner et al, 2023;McGinn et al, 2021), and watershed management practices on water resources (Mahmoodi et al, 2021b). Moreover, it has been proven to be capable of modeling in data-scarce regions (Wagner et al, 2012;Tigabu et al, 2023).…”
Section: Hydrologic Modelmentioning
confidence: 99%
“…Currently, SWAT+ is tested in few watersheds across the world, where the results from SWAT+ are favorable compared to the previous model version (Wagner et al, 2022) It can simulate the quantity and quality of water resources from a hydrological response unit to basin scale. SWAT is also suitable to assess the impact of climate change (Mahmoodi et al, 2021a), land cover change (Tigabu et al, 2019) and land use change (McGinn et al, 2021, and watershed management practices on water resources (Mahmoodi et al, 2021b) Moreover, it has been proven capable of modeling in data scarce regions (Tigabu et al, 2023, Wagner et al, 2012. To depict the spatial heterogeneity of a watershed, each watershed is divided into multiple homogenous hydrological response units based on a unique combination of land-use, slope and soil characteristics (HRU).…”
Section: Hydrologic Modelmentioning
confidence: 99%
“…In a similar proposal, Melo and Wendland (2017), when simulating the recharge volume and the water level in the outcrop zone of the Guarani Aquifer System for citrus, pasture, eucalyptus, and sugarcane areas, showed that recharge rates will be more negatively affected in the last two, especially for the sugarcane area, due to the high evapotranspiration rates of the culture. Mahmoodi et al (2021) and Wu et al (2020) show that the combined action of climate change and demand for groundwater accentuate the negative effects on aquifer systems. It is noteworthy that Wu et al (2020) demonstrate that when considering only the effects of climate change, there was an increase in aquifer storage; however, in the scenario of climate change and demand, there was storage decay.…”
Section: Groundwater and Climate Changementioning
confidence: 99%